2016
DOI: 10.1007/s10551-016-3375-4
|View full text |Cite
|
Sign up to set email alerts
|

The Frontstage and Backstage of Corporate Sustainability Reporting: Evidence from the Arctic National Wildlife Refuge Bill

Abstract: KAIST, CEIBS, the Ivey Business School, the Schulich School of Business and the Université Toulouse 1 Capitole for their valuable comments and feedback. Charles Cho also acknowledges the financial support provided by the Fonds Québécois de la Recherche sur la Société et la Culture (FQRSC), the Social Sciences and Humanities Research Council of Canada (SSHRC), and the ESSEC Research Centre (CERESSEC). Michelle Rodrigue acknowledges the financial support from Université Laval's Programme de soutien à la recherch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(118 citation statements)
references
References 96 publications
3
115
0
Order By: Relevance
“…Historically, Canadian chemical, resource, and energy sector companies have been the first to release nonfinancial reports on their environmental impacts. This is consistent with previous studies that have found that industries with higher impact (e.g., environmental degradation) engage more extensively in corporate social responsibilty (CSR) reporting (Cho, Laine, Roberts, and Rodrigue, 2018;Cho and Patten, 2007;Chung and Cho, 2018;Young and Marais, 2012).…”
Section: Industry Trendssupporting
confidence: 92%
“…Historically, Canadian chemical, resource, and energy sector companies have been the first to release nonfinancial reports on their environmental impacts. This is consistent with previous studies that have found that industries with higher impact (e.g., environmental degradation) engage more extensively in corporate social responsibilty (CSR) reporting (Cho, Laine, Roberts, and Rodrigue, 2018;Cho and Patten, 2007;Chung and Cho, 2018;Young and Marais, 2012).…”
Section: Industry Trendssupporting
confidence: 92%
“…However, these campaigns are not always articulated as solely a crusade against pollution, but rather as conflicts in defense of land rights, sovereignty, and justice (Temper et al 2015, 2018). Prominent examples include the opposition of different IPs (e.g., Inupiat, Gwich'in) across Canada and the United States to different oil drilling plans in the Arctic (Cho et al 2018), or widespread social mobilization against pipelines such as the Dakota Access Pipeline (Donaghy and Lisenby 2018), the Enbridge Pipeline (Donaghy 2018), the Trans Mountain Pipeline (CRED 2013), or the Keystone XL Pipeline (Bradshaw 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Notwithstanding the potential of Goffman's proposal for the analysis of an increasingly digital world (Vigmo & Lantz-Andersson, 2014;Leigh, 2017;Bullock, 2018;Portillo, Rudes, Viglione, & Nelson, 2013;Cho et al, 2016), there seems to be a greater plasticity in the presentation of the self in an online context, in a more fluid identity (Hanusch, 2017;Leaver & Highfield, 2018;Lyons, 2018), in which the professional, social and personal dimensions can be combined (Hanusch, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Backstage areas are, hence, like the backstage of a theatre outside the stage. Backstage allows actors to prepare their performance on stage by preparing their more formal performance to perform a role (Bute, 2016;Cain, 2012;Chen & Wang, 2018;Cho et al, 2016;Giddens, 1997;Goffman, 1993;Leigh, 2017). According to Cain (2012), -The two regions have a symbiotic relationship in that activities in the backstage allow workers to maintain appropriate behaviors during the front stage, while front stage activities provide fodder for discussions and activities in the back region‖ (p. 669).…”
Section: And 566);mentioning
confidence: 99%